2019
DOI: 10.1186/s12935-019-0818-x
|View full text |Cite
|
Sign up to set email alerts
|

MiR-591 functions as tumor suppressor in breast cancer by targeting TCF4 and inhibits Hippo-YAP/TAZ signaling pathway

Abstract: Background MicroRNAs have been involved in regulating crucial biological function in some tumors. However, the clinical role and functional effects of miR-591 in breast cancer remain unknown. Methods The expression of miR-591 was detected in breast cancer tissues and their paired normal tissues by qRT-PCR. Functional assays were performed to confirm the effects of miR-591 on the proliferation and invasion of breast cancer. Bioinformatics analysis, luciferase reporter as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 17 publications
2
14
0
Order By: Relevance
“…Previous evidence has shown that YAP1 exerts an oncogenic function in several types of human cancer, such as breast and lung cancer ( 22 , 23 ). As the findings of the present study revealed that YAP1 is upregulated in CC, it was hypothesized that YAP1 may act as an oncogenic gene in CC.…”
Section: Resultsmentioning
confidence: 99%
“…Previous evidence has shown that YAP1 exerts an oncogenic function in several types of human cancer, such as breast and lung cancer ( 22 , 23 ). As the findings of the present study revealed that YAP1 is upregulated in CC, it was hypothesized that YAP1 may act as an oncogenic gene in CC.…”
Section: Resultsmentioning
confidence: 99%
“…A previous study demonstrated that miR-495 can inhibit the progression of non-small cell lung cancer by targeting TCF4 (39). Previous research has confirmed that the inhibitory effects of miR-591 expression on breast cancer cell proliferation and invasion are mediated by TCF4 (40). Crucially, it has been found that the overexpression of miR-299-3p can inhibit CC cell growth and invasion.…”
Section: Discussionmentioning
confidence: 82%
“…Luo et al revealed that miR-212 was significantly downregulated in human osteosarcoma tissues, and ectopic miR-212 expression suppressed the proliferation and invasion of osteosarcoma cells [31], and this was subsequently validated by studies by Liu et al [32] and Li et al [33]. The miR-591 gene was initially identified as a tumor-suppressor gene due to its downregulation in breast cancer tissues, and low miR-591 expression was found to be involved in lymph node metastasis and advanced TNM stage in patients with breast cancer [34]. Further, Niu et al [35] found that miR-153 was downregulated in osteosarcoma tissues compared with normal controls, potentially acting as a tumor suppressor through negatively regulating TGF-b2 expression, which agrees with the results of Wang et al [36].…”
Section: Discussionmentioning
confidence: 88%